Transfer of Land Rights Based on A Blank Deed of Agreement Made by a Notary and Land Deeds Office (PPAT) - Syafitri, Ellana Nur; andayani, Sri Wahyu H (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
In the life of society, a provision is needed that regulates the proof of the occurrence of an event, condition or legal act, so that in civil law, an important role is needed for a deed as a written document that can provide written proof of the existence of an event, condition or legal act. Legal acts carried out by a person with written evidence are made and published in the form of an authentic deed that contains the formal truth about the existence of a legal act carried out to determine the rights and obligations of each person who carries out a legal act, achieves legal certainty, and proof of the legal act. The background is the practice of agreements for building shophouses which are stated in the Deed of Agreement through blank forms made before a Notary. The issue that arises then is whether the agreement can be accepted in positive law. The problem in this journal discusses how the Notary's Responsibility for the Deed of Agreement through blank forms and How the Legal Protection for the injured party is for the Deed that is canceled, which aims to gain an understanding regarding the validity of the Deed of Agreement. The method used is Normative Jurisprudence, Conceptual Approach Type, Using Data Collection Methods with Literature studies related to Laws and Regulations, and the Research Specifications used are Descriptive Techniques that focus on solving legal problems and events. The results of this study explain that the Notary's responsibility in making a deed of agreement through blank forms is very large, including civil, criminal, and administrative responsibilities Legal protection for parties to a deed of agreement that is canceled by law is based on the principle of justice and legal certainty guaranteed by statutory regulations.